Lithium iron phosphate positive electrode material and preparation method and application thereof
By controlling the uniformity of the carbon cladding layer and carrier mobility, the problem of insufficient performance of LiFePO4 positive electrode material during high current charging and discharging is solved, and the electrochemical performance of lithium iron phosphate positive electrode material and the cycling stability of the battery are improved.
Patent Information
- Application Number
- CN202411719693.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-28
- Publication Date
- 2024-12-31
- Estimated Expiration
- 2044-11-28
AI Technical Summary
LiFePO4 positive electrode material has low electronic conductivity and lithium ion diffusion coefficient during charging and discharging of high current, resulting in unsatisfactory rate performance. Uneven or too thick carbon coating layer will hinder the diffusion of lithium ions and affect electrochemical performance and cyclic stability.
By controlling the standard deviation of the carbon cladding thickness and carbon content of the lithium iron phosphate positive electrode material, the uniformity of the carbon cladding layer is ensured. The thickness of the carbon cladding layer is between 1 nm and 10 nm and the carbon content is between 1 wt% and 10 wt%. The shape coefficient is between 0.5 and 1, and the carrier mobility is between 20.03×10-6cm2/V·s to 21.71×10-6cm2/V·s. Iron phosphate is prepared by high-pressure atomization-high-speed stirring and hydrothermal reaction. Lithium matrix and composite carbon source.
The carrier mobility and conductivity of lithium iron phosphate positive electrode material are improved, the electrochemical performance is enhanced, including specific capacity, magnification and cycling performance, and the yield strength and compaction density of the electrode are improved.
Smart Images

Figure CN119230802A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of lithium iron phosphate positive electrode materials, and in particular to a lithium iron phosphate positive electrode material and a preparation method and application thereof. Background Art
[0002] As a new generation of lithium-ion battery cathode material, LiFePO4 material has become a hot topic of current research due to its low price, low environmental pollution, excellent thermal stability and structural stability, and high theoretical specific capacity. However, due to its own structural defects, LiFePO4 has low electronic conductivity and lithium ion diffusion coefficient, which results in it not being fully utilized during high current charging and discharging, and its rate performance is not ideal.
[0003] At present, carbon coating, ion doping and particle nano-crystallization are conventional means to improve the rate performance of lithium iron phosphate materials. However, uneven carbon coating will reduce the carrier mobility on the surface of the material and deteriorate the conductivity; too thick carbon coating will hinder the diffusion of lithium ions between the electrode and the electrolyte interface; too high carbon content will lead to too low compaction density of the material and poor fracture strength of the electrode. The above factors will affect the electrochemical performance and cycle stability of the battery corresponding to the positive electrode material.
[0004] In view of this, the present invention is proposed. Summary of the invention
[0005] The object of the present invention is to provide a lithium iron phosphate positive electrode material and a preparation method and application thereof, so as to solve or improve the above-mentioned technical problems.
[0006] The present invention can be implemented like this: In a first aspect, the present invention provides a lithium iron phosphate positive electrode material, the lithium iron phosphate positive electrode material comprising a lithium iron phosphate matrix and a carbon coating layer coated on the surface of the lithium iron phosphate matrix; The average standard deviation of the thickness of the carbon coating layer in the lithium iron phosphate cathode material is , , 0.05nm≤ σ(d) ≤0.35nm; The average standard deviation of carbon content in lithium iron phosphate positive electrode material is s ( C wt% ), , 0.02wt%≤ σ(C wt% ) ≤0.35wt%; in, N 1 is the sample size of lithium iron phosphate positive electrode material particles taken during the lithium iron phosphate positive electrode material test. N 1 ≥ 10; , The first value taken when testing lithium iron phosphate positive electrode material i The standard deviation of carbon coating thickness and carbon content corresponding to each lithium iron phosphate cathode material particle; , , n For the i The sample size of a local location taken when testing a lithium iron phosphate positive electrode material particle, n ≥5; d m For the m The thickness of the carbon coating layer corresponding to a local position, For what is taken n Local location samples d m The average value of , in nm; C m For the m The carbon content corresponding to each local position is For what is taken n Local location samples C m The average value, in wt%; The thickness of the carbon coating layer of the lithium iron phosphate cathode material is d , , 1nm≤ d ≤10nm; For the i The lithium iron phosphate positive electrode material particles are taken n Local location samples d m The average value of The carbon content of lithium iron phosphate positive electrode material is , , 1wt%≤ C ≤10wt%; For the i The lithium iron phosphate positive electrode material particles are taken n Local location samples C m The average value of .
[0007] In an optional embodiment, the shape factor of the lithium iron phosphate positive electrode material is , , 0.5≤ ≤1; in, N 2 is the sample size of lithium iron phosphate positive electrode material particles taken during the test of lithium iron phosphate positive electrode material, N 2 ≥ 10; The first value taken when testing lithium iron phosphate positive electrode material j The shape factor corresponding to each lithium iron phosphate cathode material particle; , D s For the j The diameter of the standard circle with the same projection area in the TEM two-dimensional projection image of the lithium iron phosphate positive electrode material particles is D. j The diameter of the minimum circumscribed circle of the particle projection in the TEM two-dimensional projection image of a lithium iron phosphate positive electrode material particle.
[0008] In an optional embodiment, the parameter factor of the lithium iron phosphate positive electrode material Q = , 0.07nm -1 ≤ Q ≤7nm -1 .
[0009] In an optional embodiment, the lithium iron phosphate positive electrode material further includes at least one of the following features: Feature 1: Lithium iron phosphate cathode material 0.550~0.910; Feature 2: Lithium iron phosphate cathode material 1.5nm~9.1nm; Feature 3: Lithium iron phosphate cathode material 0.055nm~0.343nm; Feature 4: Lithium iron phosphate cathode material 1.94wt%~9.68wt%; Feature 5: Lithium iron phosphate cathode material s ( C wt% ) is 0.024wt%~0.336wt%; Feature 6: Lithium iron phosphate cathode material Q 0.072nm -1 ~6.596nm -1 ; Feature 7: The specific surface area of lithium iron phosphate positive electrode material is 9.3m 2 / g~15.1m 2 / g; Feature 8: Lithium iron phosphate cathode material D 50 0.85μm~1.50μm; Feature 9: The carrier mobility of lithium iron phosphate positive electrode material is 20.03×10 -6 cm 2 / V·s~21.71×10- 6 cm 2 / V·s; Feature 10: The general formula of lithium iron phosphate matrix is Li 1-x A x Fe 1-y M y (PO 4-a )D a ; wherein A includes at least one of Na and Mg; M includes at least one of Al, Ni, Co, Mn, Ti, La, Ce, Cr, Mo, Ca, Ga, V, Nb, Zr, In, Zn and Y; D includes at least one of F and S; 0≤x≤0.1, 0≤y≤0.1 and 0≤a≤0.1.
[0010] In a second aspect, the present invention provides a method for preparing a lithium iron phosphate positive electrode material as described in any of the aforementioned embodiments, comprising the following steps: ball milling a lithium iron phosphate matrix and a composite carbon source to obtain a mixed precursor; drying the mixed precursor and sintering the mixed precursor to obtain a lithium iron phosphate positive electrode material.
[0011] In an optional embodiment, the preparation of the lithium iron phosphate positive electrode material includes at least one of the following features: Feature 11: The preparation of the lithium iron phosphate matrix includes: mixing a first solution containing a ferrous salt with a second solution containing a lithium source and a phosphate to obtain a mixed solution; adjusting the pH value of the mixed solution to 6 to 8 and then performing a hydrothermal reaction, and collecting a solid after the reaction is completed; Feature 12: The preparation of the composite carbon source comprises: mixing polyethylene glycol gel with a melted carbon source; the carbon source comprises at least one of sorbitol, erythritol, fructose, rhamnose and malic acid; the molar ratio of lithium element in the lithium iron phosphate matrix to the carbon source and polyethylene glycol is 1:(0.03-0.05):(0.02-0.04); Feature 13: Ball milling time is 1h~2h; Feature 14: The drying temperature of the mixed precursor is 90°C to 110°C; Feature 15: Drying time of the mixed precursor is 10h~14h; Feature 16: Sintering includes: first keeping warm at 400℃~550℃ for 2h~5h, and then keeping warm at 650℃~750℃ for 6h~8h.
[0012] In an optional embodiment, the preparation of the lithium iron phosphate matrix includes at least one of the following conditions: Condition 1: The general formula of lithium iron phosphate matrix is Li 1-x A x Fe 1-y M y (PO 4-a)D a , when the lithium iron phosphate matrix further contains M, A and D elements, the first solution further contains an M source, and the second solution further contains an A source and a D source; Condition 2: spraying the first solution into the second solution under stirring by high-pressure atomization; or, spraying the second solution into the first solution under stirring by high-pressure atomization; Condition 3: The temperature of the hydrothermal reaction is 150°C~180°C; Condition 4: The hydrothermal reaction time is 8h~10h.
[0013] In an optional embodiment, the ferrous salt includes at least one of ferrous oxalate, ferrous chloride and ferrous acetate; Or, the lithium source includes at least one of lithium oxalate, lithium chloride and lithium acetate; or, the phosphate includes at least one of diammonium phosphate and ammonium hydrogen phosphate; Or, the M source is a water-soluble salt of the M element; Or, source A includes at least one of sodium fluoride, magnesium fluoride, sodium chloride, magnesium chloride and sodium sulfide; or, the D source comprises at least one of ammonium fluoride, lithium fluoride, ammonium sulfide, lithium sulfide, ammonium bisulfite and thiourea; Or, the ratio of the total molar number of the iron element in the ferrous salt to the M element in the M source, the total molar number of the lithium element in the lithium source to the A element in the A source, and the molar number of the P element in the phosphate is 1:1:(0.95~1.1); wherein the molar ratio of the lithium element to the A element is (0.9~1):(0~0.1); the molar ratio of the iron element to the M element is (0.9~1):(0~0.1); the molar ratio of the oxygen element in the phosphate to the D element in the D source is (3.9~4):(0~0.1); Or, the nozzle diameter of the high-pressure atomization spray gun used for high-pressure atomization is 0.3mm~0.6mm, and the operating pressure is 0.2MPa~0.4MPa; Or, the stirring condition corresponds to a stirring rate of 600 r / min~1000 r / min.
[0014] In a third aspect, the present invention provides a positive electrode plate, wherein the active material in the positive electrode plate includes the lithium iron phosphate positive electrode material of the aforementioned embodiment.
[0015] In a fourth aspect, the present invention provides a battery comprising the positive electrode sheet of the aforementioned embodiment.
[0016] The beneficial effects of the present invention include: The standard deviation of the carbon coating thickness proposed by the present invention σ(d) i and carbon content standard deviation s (C wt% ) i The thickness of the carbon coating layer at different positions of the lithium iron phosphate positive electrode material particles and the dispersion of the carbon content relative to their respective average values are respectively reflected to characterize the uniformity of the carbon coating layer on the surface of the lithium iron phosphate matrix. The uniform coating of the carbon coating layer on the surface of the lithium iron phosphate matrix can inhibit the fusion of grains and the growth of particles, thereby achieving the purpose of controlling the particle size and curbing particle agglomeration. The average standard deviation of the carbon coating layer thickness σ(d) and the average standard deviation of carbon content s ( C wt% ) can measure the uniformity of carbon layer distribution on the surface of lithium iron phosphate positive electrode material. σ(d) and σ ( C wt% ) is smaller, the more uniform the carbon coating on the material surface is, and the better the conductivity of the material is; σ(d) and σ ( C wt% ) value, the higher the uniformity of the carbon coating, which leads to the deterioration of the charge and discharge performance of the positive electrode material.
[0017] In addition, the thickness of the carbon coating layer of the lithium iron phosphate cathode material and carbon content The value of must be within an appropriate range; The higher the value, the more unfavorable it is for lithium ions to be inserted and removed and diffused between the electrode and electrolyte interface; The higher it is, the easier it is to inhibit the formation of crystalline LiFePO4 phase and reduce the compaction density of the material.
[0018] The lithium iron phosphate positive electrode material provided by the present invention has σ(d)、σ ( C wt% ), as well as The present invention provides σ(d)、σ ( C wt% ), as well as The range of the present invention is that the carbon coating layer has a uniform carbon coating layer, the thickness of the carbon coating layer and the carbon content at each position are relatively consistent, which is beneficial to improving the carrier mobility and conductivity of the lithium iron phosphate positive electrode material, and is beneficial to further improving the electrochemical performance of the battery prepared from the lithium iron phosphate positive electrode material. BRIEF DESCRIPTION OF THE DRAWINGS
[0019] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the drawings required for use in the embodiments are briefly introduced below. It should be understood that the following drawings only show certain embodiments of the present invention and therefore should not be regarded as limiting the scope. For ordinary technicians in this field, other related drawings can be obtained based on these drawings without creative work.
[0020] Figure 1 TEM image of the lithium iron phosphate positive electrode material prepared in Example 6; Figure 2 This is the TEM image of the lithium iron phosphate positive electrode material prepared in Comparative Example 4. DETAILED DESCRIPTION
[0021] In order to make the purpose, technical scheme and advantages of the embodiments of the present invention clearer, the technical scheme in the embodiments of the present invention will be described clearly and completely below. If the specific conditions are not specified in the embodiments, they are carried out according to conventional conditions or conditions recommended by the manufacturer. If the manufacturer of the reagents or instruments used is not specified, they are all conventional products that can be purchased commercially.
[0022] The lithium iron phosphate positive electrode material provided by the present invention and its preparation method and application are described in detail below.
[0023] The invention provides a lithium iron phosphate positive electrode material. The lithium iron phosphate positive electrode material comprises a lithium iron phosphate matrix and a carbon coating layer coated on the surface of the lithium iron phosphate matrix.
[0024] Among them, the average standard deviation of the thickness of the carbon coating layer in the lithium iron phosphate positive electrode material is , , 0.05nm≤ σ(d) ≤0.35nm; The average standard deviation of carbon content in lithium iron phosphate positive electrode material is s ( C wt% ), , 0.02wt%≤ σ(C wt% ) ≤0.35wt%; in, N 1 is the sample size of lithium iron phosphate positive electrode material particles taken during the lithium iron phosphate positive electrode material test. N 1 ≥ 10; , The first value taken when testing lithium iron phosphate positive electrode material i The standard deviation of carbon coating thickness and carbon content corresponding to each lithium iron phosphate cathode material particle; , , n For the i The sample size of a local location taken when testing a lithium iron phosphate positive electrode material particle, n ≥5; d m For the m The thickness of the carbon coating layer corresponding to a local position, For what is taken n Local location samples d m The average value of , in nm; C m For the m The carbon content corresponding to each local position is For what is taken n Local location samples C m The average value, in wt%; The thickness of the carbon coating layer of the lithium iron phosphate cathode material is d , , 1nm≤ d ≤10nm; The carbon content of lithium iron phosphate positive electrode material is , , 1wt%≤ C ≤10wt%; For the i The lithium iron phosphate positive electrode material particles are taken n Local location samples d m The average value of For the i The lithium iron phosphate positive electrode material particles are taken n Local location samples C m The average value of .
[0025] The selection of the local position of the above-mentioned lithium iron phosphate positive electrode material particles is random selection. In some preferred embodiments, the random selection does not specifically define a range, and the selection is not concentrated in a smaller range or area of the particles. The sample selection range preferably covers the entire positive electrode material particle.
[0026] Carbon coating thickness standard deviation σ(d) i and carbon content standard deviation s ( C wt% ) iIt reflects the thickness of the carbon coating layer at different positions of the lithium iron phosphate positive electrode material particles and the dispersion of the carbon content relative to their respective average values, so as to characterize the uniformity of the carbon coating layer on the surface of the lithium iron phosphate matrix particles. σ(d) i Japanese ( C wt% ) i The smaller the value is, the smaller the dispersion of the carbon coating thickness and carbon content on the surface of the positive electrode material particles relative to their respective average values is, the more uniform the carbon coating is, and the better the conductivity of the material is; σ(d) i Japanese ( C wt% ) i The higher the value, the greater the dispersion of the carbon coating thickness and carbon content on the surface of the positive electrode material particles relative to their respective average values, indicating that the uniformity of the carbon coating is worse and the charge and discharge performance of the material is also worse. Furthermore, the average standard deviation of the carbon coating thickness σ(d) and the average standard deviation of carbon content s ( C wt% ) also conforms to the above-mentioned variation law and its numerical value can measure the uniformity of the carbon layer distribution on the surface of the lithium iron phosphate positive electrode material.
[0027] In addition, the thickness of the carbon coating layer of the lithium iron phosphate cathode material and carbon content The value of must be within an appropriate range. The higher the value, the more unfavorable it is for lithium ions to be inserted and removed and diffused between the electrode and electrolyte interface; The higher it is, the easier it is to inhibit the formation of crystalline LiFePO4 phase and reduce the compaction density of the material.
[0028] In continuation of the above, the present invention provides a satisfying σ(d)、σ ( C wt% ), as well as The lithium iron phosphate positive electrode material in the range has a uniform carbon coating layer, and the thickness of the carbon coating layer and the carbon content at each position are relatively consistent, which is beneficial to improving the carrier mobility and conductivity of the lithium iron phosphate positive electrode material, and is beneficial to further improving the electrochemical performance of the battery prepared from the lithium iron phosphate positive electrode material.
[0029] In some optional embodiments, the lithium iron phosphate positive electrode material It can be 1.5nm~9.1nm, such as 1.5nm, 1.6nm, 1.7nm, 2.7nm, 3.0nm, 3.8nm, 4.6nm, 5.5nm, 6.3nm, 8.7nm or 9.1nm, or other values within the range of 1.5nm~9.1nm.
[0030] In some optional embodiments, the lithium iron phosphate positive electrode material It can be 0.055nm~0.343nm, such as 0.055nm, 0.063nm, 0.101nm, 0.112nm, 0.116nm, 0.136nm, 0.210nm, 0.254nm, 0.304nm, 0.308nm, 0.310nm, 0.314nm, 0.338nm or 0.343nm, or other values within the range of 0.055nm~0.343nm.
[0031] In some optional embodiments, the lithium iron phosphate positive electrode material It can be 1.94wt%~9.68wt%, such as 1.94wt%, 1.95wt%, 1.96wt%, 1.97wt%, 1.98wt%, 1.99wt%, 3.47wt%, 3.75wt%, 4.75wt%, 5.15wt%, 6.25wt%, 7.55wt%, 9.23wt% or 9.68wt%, etc., or it can be other values within the range of 1.94wt%~9.68wt%.
[0032] In some optional embodiments, the lithium iron phosphate positive electrode material s ( C wt% ) can be 0.024wt%~0.336wt%, such as 0.024wt%, 0.040wt%, 0.089wt%, 0.105wt%, 0.107wt%, 0.130wt%, 0.204wt%, 0.240wt%, 0.296wt%, 0.298wt%, 0.301wt%, 0.306wt%, 0.325wt% or 0.336wt%, etc., or other values within the range of 0.024wt%~0.336wt%.
[0033] In some optional embodiments, the shape factor of the lithium iron phosphate positive electrode material is , , 0.5≤ ≤1; in, N 2 is the sample size of lithium iron phosphate positive electrode material particles taken during the test of lithium iron phosphate positive electrode material, N 2 ≥ 10; The first value taken when testing lithium iron phosphate positive electrode material j The shape factor corresponding to each lithium iron phosphate cathode material particle; , D s For the j The diameter of the standard circle with the same projection area in the TEM two-dimensional projection image of the lithium iron phosphate positive electrode material particles is D. j The diameter of the minimum circumscribed circle of the particle projection in the TEM two-dimensional projection image of a lithium iron phosphate positive electrode material particle.
[0034] Form Factor , indicating that the shape of the lithium iron phosphate cathode material particles is similar to that of a standard sphere ( =1), The closer the value of is to 1, the closer the particle morphology is to a sphere and the more regular the particle morphology is. The closer the value is to 1, the more regular the morphology of the lithium iron phosphate cathode material particles is, the more uniform the particle size of the lithium iron phosphate cathode material particles is, the better the particle dispersion is, and the more conducive to the diffusion and transmission of lithium ions and electrons is. The smaller the value, the worse the morphology regularity of the lithium iron phosphate positive electrode material particles, the more serious the agglomeration between the particles, and the electrochemical performance of the battery made therefrom is affected.
[0035] In continuation of the above, the present invention provides a satisfying The particle morphology of the lithium iron phosphate positive electrode material in the range is regular, and the uniform particle morphology is not only beneficial to the diffusion of lithium ions, but also beneficial to improving the yield strength of the electrode prepared from the lithium iron phosphate positive electrode material, and improving the electrochemical performance of the battery prepared from the above electrode.
[0036] In some optional embodiments, the lithium iron phosphate positive electrode material It can be 0.550-0.910, such as 0.550, 0.670, 0.673, 0.677, 0.695, 0.702, 0.712, 0.761, 0.858, 0.880, 0.893, 0.907 or 0.910, or other values within the range of 0.550-0.910.
[0037] In some optional embodiments, the carrier mobility of the lithium iron phosphate positive electrode material can be 20.03×10 - 6 cm 2 / V·s~21.71×10 -6 cm 2 / V·s, such as 20.03×10 -6 cm2 / V·s、21.05×10 -6 cm 2 / V·s、20.20×10 -6 cm 2 / V·s、20.26×10 -6 cm 2 / V·s, 20.29×10 -6 cm 2 / V·s、20.30×10 -6 cm 2 / V·s, 20.33×10 -6 cm 2 / V·s、20.42×10 -6 cm 2 / V·s、20.50×10 -6 cm 2 / V·s、20.60×10 -6 cm 2 / V·s, 20.62×10 -6 cm 2 / V·s, 20.86×10 -6 cm 2 / V·s, 21.38×10 -6 cm 2 / V·s or 21.71×10 -6 cm 2 / V·s, etc., can also be 20.03×10 -6 cm 2 / V·s~21.71×10 -6 cm 2 / V·s range.
[0038] In some optional embodiments, the parameter factor of the lithium iron phosphate positive electrode material Q = , 0.07nm -1 ≤ Q ≤7nm -1 .
[0039] The above parameter factors and , and s ( C wt% ) can comprehensively reflect the electrochemical performance of the battery corresponding to the lithium iron phosphate positive electrode material. The closer it is to 1 (i.e. the more regular the particle morphology), and and s ( C wt%) is smaller (i.e. the carbon coating on the surface of the material is more uniform), the parameter factor obtained at this time Q The larger the value, the better the electrochemical performance of the battery corresponding to the lithium iron phosphate positive electrode material.
[0040] In some optional embodiments, the lithium iron phosphate positive electrode material Q Can be 0.072nm -1 ~6.596nm -1 , such as 0.072nm -1 , 0.073nm -1 , 0.074nm -1 、0.076nm -1 、0.079nm -1 、0.111nm -1 , 0.205nm -1 , 0.505nm -1 、0.540nm -1 、0.648nm -1 , 1.012nm -1 、3.405nm -1 or 6.596nm -1 etc., can also be 0.072nm -1 ~6.596nm -1 Other values within the range.
[0041] In continuation of the above, the present invention provides ,s ( C wt% ), as well as Q The lithium iron phosphate positive electrode material within the value range has a regular particle morphology and a uniform carbon coating layer, which can make the battery using it as the positive electrode material have better electrochemical properties (such as specific capacity, rate and cycle performance, etc.).
[0042] In some optional embodiments, the specific surface area of the lithium iron phosphate positive electrode material can be 9.3 m 2 / g~15.1m 2 / g, such as 9.3m 2 / g, 10.2m 2 / g, 11.7m 2 / g, 11.9m 2 / g, 12.0m 2 / g, 12.1m 2 / g, 12.3m 2 / g, 12.4m 2 / g, 12.6m 2 / g, 12.8m 2 / g, 13.2m 2 / g, 13.7m 2 / g, 14.3m 2 / g or 15.1m 2 / g, etc., can also be 9.3m 2 / g~15.1m 2 / Other values within the range of g.
[0043] In some optional embodiments, the lithium iron phosphate positive electrode material D 50 It can be 0.85μm~1.50μm, such as 0.85μm, 0.90μm, 0.96μm, 1.00μm, 1.04μm, 1.07μm, 1.06μm, 1.08μm, 1.10μm, 1.12μm, 1.14μm, 1.16μm, 1.35μm or 1.50μm, etc., or other values within the range of 0.85μm~1.50μm.
[0044] In some optional embodiments, the general formula of the lithium iron phosphate matrix can be Li 1-x A x Fe 1-y M y (PO 4-a )D a Wherein, A may include at least one of Na and Mg, for example; M may include at least one of Al, Ni, Co, Mn, Ti, La, Ce, Cr, Mo, Ca, Ga, V, Nb, Zr, In, Zn and Y, for example; D may include at least one of F and S, for example; 0≤x≤0.1, 0≤y≤0.1 and 0≤a≤0.1.
[0045] Accordingly, the present invention also provides a method for preparing the above-mentioned lithium iron phosphate positive electrode material, which may include the following steps: ball milling the lithium iron phosphate matrix and the composite carbon source to obtain a mixed precursor; drying and sintering the mixed precursor to obtain the lithium iron phosphate positive electrode material.
[0046] In some optional embodiments, the preparation of the lithium iron phosphate matrix may include: mixing a first solution containing a ferrous salt with a second solution containing a lithium source and a phosphate to obtain a mixed solution; adjusting the pH value of the mixed solution to 6-8 and then performing a hydrothermal reaction, and collecting the solid after the reaction is completed.
[0047] The ferrous salt may illustratively but not limitatively include at least one of ferrous oxalate, ferrous chloride and ferrous acetate.
[0048] The lithium source may illustratively but not limitatively include at least one of lithium oxalate, lithium chloride, and lithium acetate.
[0049] The phosphate salt may illustratively but not limitatively include at least one of diammonium phosphate and ammonium hydrogen phosphate.
[0050] In the present invention, when the lithium iron phosphate matrix further contains M element, the M source exists in the first solution; when the lithium iron phosphate matrix further contains at least one of A element and D element, the corresponding A source and D source exist in the second solution.
[0051] For example, the lithium iron phosphate matrix also contains M, A and D elements, the first solution containing ferrous salt also contains M source, and the second solution containing lithium source and phosphate also contains A source and D source. Under this condition, the ferrous salt and M source can be dispersed in deionized water, and nitrogen can be blown for a period of time (such as 1 hour) under stirring to remove dissolved oxygen in the solution to obtain the first solution. Correspondingly, the lithium source, phosphate, A source and D source can be dispersed in deionized water, and stirred at high speed under the protection of nitrogen atmosphere to obtain the second solution.
[0052] The M source may be a water-soluble salt of the M element.
[0053] The A source may illustratively but not limitatively include at least one of sodium fluoride, magnesium fluoride, sodium chloride, magnesium chloride, and sodium sulfide.
[0054] The D source may illustratively but not limitatively include at least one of ammonium fluoride, lithium fluoride, ammonium sulfide, lithium sulfide, ammonium bisulfite, and thiourea.
[0055] In some optional embodiments, the ratio of the total molar number of iron element in the ferrous salt and the total molar number of M element in the M source, the total molar number of lithium element in the lithium source and the A element in the A source, and the molar number of P element in the phosphate is 1:1:(0.95~1.1), such as 1:1:0.95, 1:1:0.96, 1:1:0.97, 1:1:0.98, 1:1:0.99, 1:1:1, 1:1:1.05 or 1:1:1.1, etc., and can also be other values within the range of 1:1:(0.95~1.1).
[0056] In some optional embodiments, the molar ratio of lithium element to A element can be (0.9~1):(0~0.1), such as 0.9:0.1, 0.95:0.0.5 or 1:0, etc., or other values within the range of (0.9~1):(0~0.1).
[0057] In some optional embodiments, the molar ratio of the iron element to the M element can be (0.9~1):(0~0.1), such as 0.9:0.1, 0.95:0.0.5 or 1:0, etc., or other values within the range of (0.9~1):(0~0.1).
[0058] In some optional embodiments, the molar ratio of the oxygen element in the phosphate to the D element in the D source can be (3.9~4):(0~0.1), such as 3.9:0.1, 3.95:0.05 or 4:0, etc., or other values within the range of (3.9~4):(0~0.1).
[0059] In some optional embodiments, the first solution can be sprayed into the second solution under stirring conditions by high pressure atomization. In some other optional embodiments, the second solution can also be sprayed into the first solution under stirring conditions by high pressure atomization.
[0060] Among them, the nozzle diameter of the high-pressure atomization spray gun used for high-pressure atomization can be 0.3mm~0.6mm, such as 0.3mm, 0.35mm, 0.4mm, 0.45mm, 0.5mm, 0.55mm or 0.6mm, etc., or other values within the range of 0.3mm~0.6mm.
[0061] The operating pressure of high-pressure atomization can be 0.2MPa~0.4MPa, such as 0.2MPa, 0.25MPa, 0.3MPa, 0.35MPa or 0.4MPa, etc., and can also be other values within the range of 0.2MPa~0.4MPa.
[0062] In some optional embodiments, the stirring rate corresponding to the stirring condition can be 600r / min~1000r / min, such as 600r / min, 650r / min, 700r / min, 750r / min, 800r / min, 850r / min, 900r / min, 950r / min or 1000r / min, etc., or it can be other values within the range of 600r / min~1000r / min.
[0063] In some optional embodiments, ammonia water may be used to adjust the pH value of the mixed solution. The pH value may be adjusted to 6, 6.5, 7, 7.5 or 8, or other values within the range of 6 to 8.
[0064] After adjusting the pH value, stirring can be continued for a period of time at room temperature and under the protection of an inert atmosphere (such as a nitrogen atmosphere), and then transferred to a stainless steel high-pressure reactor lined with polytetrafluoroethylene for a hydrothermal reaction. After the reaction is completed, the product is cooled to room temperature and filtered, and the filtered solid phase is then centrifuged and washed with deionized water and anhydrous ethanol, and finally dried to obtain a lithium iron phosphate matrix.
[0065] The temperature of the hydrothermal reaction may be 150°C to 180°C, such as 150°C, 155°C, 160°C, 165°C, 170°C, 175°C or 180°C, or other values within the range of 150°C to 180°C.
[0066] The time of the hydrothermal reaction can be 8 h to 10 h, such as 8 h, 8.5 h, 9 h, 9.5 h or 10 h, etc., or other values within the range of 8 h to 10 h.
[0067] The drying temperature may be 60°C to 80°C, such as 60°C, 65°C, 70°C, 75°C or 80°C, etc., or other values within the range of 60°C to 80°C.
[0068] The drying time may be 10 h to 14 h, such as 10 h, 10.5 h, 11 h, 11.5 h or 12 h, etc., or other values within the range of 10 h to 14 h.
[0069] In the above, the present invention pours the first solution (or the second solution) into a high-pressure atomizing spray gun, atomizes it through a high-pressure nozzle, and sprays it into the second solution (or the first solution) stirred at a high speed in an atomized state to obtain a uniform seed precursor solution, and then adjusts the pH value with ammonia water, places it in a high-pressure reactor for hydrothermal reaction, and obtains lithium iron phosphate matrix particles. The high-pressure atomization-high-speed stirring method can enhance the initial microscopic mixing and uniform dispersion of ferrous ions, lithium ions and phosphate ions, effectively alleviate the rate difference of lithium iron phosphate nucleus formation caused by excessive local concentration of reactive ions, and provide a uniform microscopic nucleation environment for the generation of seed precursors. The seed is further subjected to hydrothermal reaction to form a lithium iron phosphate matrix with concentrated particle size distribution, good dispersibility and uniform morphology.
[0070] In some optional embodiments, the preparation of the composite carbon source may include: mixing polyethylene glycol gel with a melted carbon source.
[0071] The carbon source may illustratively but not limitatively include at least one of sorbitol, erythritol, fructose, rhamnose and malic acid.
[0072] The molar ratio of lithium element to carbon source and polyethylene glycol in the lithium iron phosphate matrix can be 1:(0.03~0.05):(0.02~0.04), such as 1:0.03:0.02, 1:0.03:0.03, 1:0.03:0.04, 1:0.04:0.02, 1:0.04:0.03, 1:0.04:0.04, 1:0.05:0.02, 1:0.05:0.03 or 1:0.05:0.04, etc., or it can be other values within the range of 1:(0.03~0.05):(0.02~0.04).
[0073] The carbon source can be heated to 130° C. to 150° C. in a high-temperature electric furnace for melting. Specifically, the melting temperature can be set according to the selected carbon source to achieve melting of the carbon source.
[0074] The polyethylene glycol gel can be prepared by dissolving polyethylene glycol powder in dimethyl sulfoxide, stirring evenly, and then heating the mixture to 50° C. to 60° C. in a water bath. In addition, the polyethylene glycol gel can be prepared by other methods and conditions.
[0075] In some optional embodiments, the ball milling time of the lithium iron phosphate matrix and the composite carbon source can be 1 h to 2 h, such as 1 h, 1.5 h or 2 h.
[0076] In some optional embodiments, the drying temperature of the mixed precursor may be 90°C to 110°C, such as 90°C, 95°C, 100°C, 105°C or 110°C, or other values within the range of 90°C to 110°C.
[0077] The drying time of the mixed precursor may be 10 h to 14 h, such as 10 h, 11 h, 12 h, 13 h or 14 h, etc., or may be other values within the range of 10 h to 14 h.
[0078] In some optional embodiments, the dried mixed precursor is first ground and pulverized, and then the fully ground precursor is placed in a muffle furnace filled with high-purity argon gas for sintering.
[0079] The sintering process includes a first stage and a second stage, wherein the first stage can be kept at 400℃~550℃ (such as 400℃, 420℃, 450℃, 480℃, 500℃, 520℃ or 550℃, etc.) for 2h~5h (such as 2h, 3h, 4h or 5h, etc.), and the second stage can be kept at 650℃~750℃ (such as 650℃, 680℃, 700℃, 720℃ or 750℃, etc.) for 6h~8h (such as 6h, 7h or 8h, etc.).
[0080] In order to further improve the conductivity and crystallinity of lithium iron phosphate, the present invention first mixes the molten carbon source with polyethylene glycol gel to obtain a composite carbon source, and then mixes it with the lithium iron phosphate matrix by ball milling, dries it, and places it in a muffle furnace for low-temperature and high-temperature roasting to obtain a lithium iron phosphate positive electrode material. In this process, the molten carbon source and polyethylene glycol gel are used as composite carbon sources to carbon-coat the lithium iron phosphate matrix. Compared with the traditional solid phase method, the molten carbon source can be easily wrapped and coated on the surface of the lithium iron phosphate matrix. The carbon network structure formed by the polyethylene glycol gel during the drying and calcination process can keep the carbon coating layer coated on the particle surface stable to form a uniform carbon coating layer. In addition, compared with water solvents, dimethyl sulfoxide has lower viscosity and surface tension. Polyethylene glycol gel is prepared using it as a solvent. After the lithium iron phosphate matrix is mixed with the composite carbon source, the good wettability of dimethyl sulfoxide can more evenly coat the molten carbon source on the surface of the lithium iron phosphate matrix and penetrate into its micropores.
[0081] In summary, the preparation method provided by the present invention can prepare a lithium iron phosphate positive electrode material with regular morphology and uniform carbon coating.
[0082] In addition, the present invention also provides a positive electrode plate, in which the active material includes the above-mentioned lithium iron phosphate positive electrode material.
[0083] The present invention also provides a battery cell, which includes the above-mentioned positive electrode plate.
[0084] For example, the battery cells may be used in, but are not limited to, electrical devices such as vehicles, ships or aircraft.
[0085] The present invention also provides a battery comprising the battery monomer.
[0086] The present invention also provides an electric device, which includes the above-mentioned battery cell and / or battery. As an example, the electric device can be, but not limited to, a mobile phone, a tablet, a laptop computer, an electric toy, an electric tool, a battery car, an electric car, a ship, a spacecraft, etc. Among them, the electric toy can include a fixed or mobile electric toy, such as a game console, an electric car toy, an electric ship toy, and an electric airplane toy, etc., and the spacecraft can include an airplane, a rocket, a space shuttle, and a spacecraft, etc.
[0087] The features and performance of the present invention are further described in detail below in conjunction with the embodiments.
[0088] Example 1 The difference between this embodiment and the following embodiment 3 is that: In S1, the ferrous salt is ferrous chloride, the lithium source is lithium acetate, and the phosphate is ammonium dihydrogen phosphate; the nozzle diameter of the high-pressure atomizing spray gun is 0.7 mm, and the operating pressure is 0.1 MPa; the stirring speed of the high-speed stirring is 550 rpm; the pH value is adjusted to 6; and the insulation time in the electric blast oven is 9 hours; In S2, the melting temperature of rhamnose is 120°C; In S3, the molar ratio of Li element in the lithium iron phosphate matrix to rhamnose and polyethylene glycol is 1:0.04:0.02; and the temperature of the first stage of sintering is 450°C.
[0089] Example 2 The difference between this embodiment and the following embodiment 3 is that: In S1, the ferrous salt is ferrous chloride, the lithium source is lithium acetate, and the phosphate is ammonium dihydrogen phosphate; the nozzle diameter of the high-pressure atomizing spray gun is 0.6 mm, and the operating pressure is 0.2 MPa; the stirring speed of the high-speed stirring is 650 rpm; the pH value is adjusted to 6; and the insulation time in the electric blast oven is 9 hours; In S2, the melting temperature of rhamnose is 130°C; In S3, the molar ratio of Li element in the lithium iron phosphate matrix to rhamnose and polyethylene glycol is 1:0.04:0.02; and the temperature of the first stage of sintering is 450°C.
[0090] Example 3 This embodiment provides a lithium iron phosphate positive electrode material, and the preparation method thereof includes: S1: preparing a lithium iron phosphate matrix.
[0091] Weigh ferrous acetate and disperse it in deionized water, and blow nitrogen for 1 hour under stirring to remove dissolved oxygen in the solution to obtain a first solution. Weigh lithium oxalate and ammonium hydrogen phosphate and disperse them in deionized water, and stir them at a high speed under nitrogen atmosphere protection at a stirring rate of 600 r / min to obtain a second solution. The molar ratio of the Li element in lithium oxalate, the Fe element in ferrous acetate, and the P element in ammonium hydrogen phosphate is 1:1:0.95.
[0092] The first solution is poured into a high-pressure atomizing spray gun with a nozzle diameter of 0.5 mm and an operating pressure of 0.3 MPa, and after being atomized by the high-pressure nozzle, it is sprayed into the second solution stirred at high speed to obtain a mixed solution. The pH value of the obtained mixed solution is adjusted to 7 with ammonia water, and it is continuously stirred for 30 minutes at room temperature and under the protection of nitrogen atmosphere, and then transferred to a stainless steel high-pressure reactor lined with polytetrafluoroethylene, and placed in an electric heating blast oven at 150°C for 8 hours. After the reaction is completed, the product is cooled to room temperature and filtered, and the filtered solid phase is centrifuged and washed with deionized water and anhydrous ethanol successively, and finally dried in a vacuum oven at 70°C for 12 hours to obtain a lithium iron phosphate matrix.
[0093] S2: preparing a composite carbon source.
[0094] Weigh rhamnose and place it in a high-temperature electric furnace, heat it to 135°C to melt it; weigh polyethylene glycol powder and dissolve it in dimethyl sulfoxide, stir it evenly, heat the mixture to 50°C and heat it in a water bath to obtain polyethylene glycol gel; mix the melted rhamnose with the polyethylene glycol gel to obtain a composite carbon source.
[0095] S3: Prepare lithium iron phosphate positive electrode material.
[0096] The lithium iron phosphate matrix in S1 and the composite carbon source in S2 are ball-milled and mixed for 1.5 hours to obtain a mixed precursor; the mixed precursor is placed in a vacuum oven at 100° C. and dried for 12 hours, and ground and crushed; then, the fully ground mixed precursor is placed in a muffle furnace filled with high-purity argon gas for sintering to obtain a lithium iron phosphate positive electrode material.
[0097] The molar ratio of Li element to rhamnose and polyethylene glycol in the lithium iron phosphate matrix is 1:0.035:0.02.
[0098] The sintering process includes: heating to 400°C at a rate of 5°C / min, keeping the temperature for 2 hours; then continuing to heat to 650°C, and the calcination time is 6 hours.
[0099] Example 4 The difference between this embodiment and embodiment 3 is that: In S1, the molar ratio of Li element in lithium oxalate, Fe element in ferrous acetate and P element in ammonium hydrogen phosphate is 1:1:1; the nozzle diameter of the high-pressure atomizing spray gun is 0.45 mm, and the operating pressure is 0.3 MPa; the stirring speed of the high-speed stirring is 700 rpm; In S2, the carbon source is sorbitol, and the melting temperature of sorbitol is 145°C; the water bath heating temperature of polyethylene glycol is 60°C; In S3, the molar ratio of Li element in the lithium iron phosphate matrix to sorbitol and polyethylene glycol is 1:0.05:0.04; the temperature of the first stage of sintering is 550°C and the time is 5h; the temperature of the second stage of sintering is 750°C and the time is 8h.
[0100] Example 5 The difference between this embodiment and embodiment 3 is that: In S1, the ferrous salt is ferrous chloride, the lithium source is lithium acetate, and the phosphate is ammonium dihydrogen phosphate; the molar ratio of the Li element in lithium acetate, the Fe element in ferrous chloride, and the P element in ammonium dihydrogen phosphate is 1:1:1; the nozzle diameter of the high-pressure atomizing spray gun is 0.4 mm, and the operating pressure is 0.35 MPa; the stirring speed of the high-speed stirring is 800 rpm; the insulation temperature in the electric blast oven is 155°C, and the insulation time is 9 hours; In S2, the melting temperature of rhamnose is 150°C; the water bath heating temperature of polyethylene glycol is 55°C; In S3, the molar ratio of Li element in the lithium iron phosphate matrix to rhamnose and polyethylene glycol is 1:0.05:0.03; the temperature of the first stage of sintering is 500°C and the time is 3h; the temperature of the second stage of sintering is 700°C and the time is 7h.
[0101] Example 6 The difference between this embodiment and embodiment 3 is that: In S1, the ferrous salt is ferrous chloride, the lithium source is lithium acetate, and the phosphate is ammonium dihydrogen phosphate; the molar ratio of the Li element in lithium acetate, the Fe element in ferrous chloride, and the P element in ammonium dihydrogen phosphate is 1:1:1.1; the nozzle diameter of the high-pressure atomizing spray gun is 0.4 mm, and the operating pressure is 0.35 MPa; the stirring speed of the high-speed stirring is 900 rpm; the pH value is adjusted to 8; the insulation temperature in the electric blast oven is 160°C, and the insulation time is 9 hours; In S2, the melting temperature of rhamnose is 150°C; the water bath heating temperature of polyethylene glycol is 60°C; In S3, the molar ratio of Li element in the lithium iron phosphate matrix to rhamnose and polyethylene glycol is 1:0.05:0.025; the temperature of the first stage of sintering is 500°C and the time is 3h; the time of the second stage of sintering is 7h.
[0102] Example 7 The difference between this embodiment and embodiment 3 is that: In S1, the ferrous salt is ferrous chloride, the lithium source is lithium acetate, and the phosphate is ammonium dihydrogen phosphate; the first solution also contains nickel chloride; the ratio of the molar number of Li element in lithium acetate, the total molar number of Fe element in ferrous chloride and Ni element in nickel chloride to the molar number of P element in ammonium dihydrogen phosphate is 1:1:0.95, wherein the molar ratio of Fe element in ferrous chloride to Ni element in nickel chloride is 0.985:0.015; the nozzle diameter of the high-pressure atomizing spray gun is 0.3 mm, and the operating pressure is 0.35 MPa; the stirring speed of the high-speed stirring is 950 rpm; the pH value is adjusted to 8; the insulation temperature in the electric blast oven is 170°C, and the insulation time is 9 hours; In S2, the carbon source is sorbitol, and the melting temperature of sorbitol is 140°C; In S3, the molar ratio of Li element in the lithium iron phosphate matrix to sorbitol and polyethylene glycol is 1:0.045:0.02; and the temperature of the first stage of sintering is 450°C.
[0103] Example 8 The difference between this embodiment and embodiment 3 is that: In S1, the ferrous salt is ferrous chloride, the lithium source is lithium acetate, and the phosphate is ammonium dihydrogen phosphate; the second solution also contains ammonium fluoride; the molar ratio of the Li element in lithium acetate, the Fe element in ferrous chloride and the P element in ammonium dihydrogen phosphate is 1:1:1; the molar ratio of the oxygen element in ammonium dihydrogen phosphate to the F element in ammonium fluoride is 3.998:0.002; the nozzle diameter of the high-pressure atomizing spray gun is 0.3 mm, and the operating pressure is 0.4 MPa; the stirring speed of the high-speed stirring is 950 rpm; the insulation temperature in the electric blast oven is 175°C, and the insulation time is 10 hours; In S2, the carbon source is sorbitol; the melting temperature of sorbitol is 145°C; the water bath heating temperature of polyethylene glycol is 55°C; In S3, the molar ratio of Li element in the lithium iron phosphate matrix to sorbitol and polyethylene glycol is 1:0.05:0.02; the temperature of the first stage of sintering is 480°C and the time is 3h; the temperature of the second stage of sintering is 680°C.
[0104] Example 9 The difference between this embodiment and embodiment 3 is that: In S1, the ferrous salt is ferrous chloride, the lithium source is lithium acetate, and the phosphate is ammonium dihydrogen phosphate; the second solution also contains sodium chloride; the ratio of the total molar number of the Li element in lithium acetate to the Na element in sodium chloride, the molar number of the Fe element in ferrous chloride to the molar number of the P element in ammonium dihydrogen phosphate is 1:1:0.95; the molar ratio of the Li element in lithium acetate to the Na element in sodium chloride is 0.985:0.015; the nozzle diameter of the high-pressure atomizing spray gun is 0.3 mm, and the operating pressure is 0.4 MPa; the stirring speed of the high-speed stirring is 1000 rpm; the insulation temperature in the electric blast oven is 180°C, and the insulation time is 10 hours; In S2, the carbon source is fructose; the melting temperature of fructose is 145°C; the water bath heating temperature of polyethylene glycol is 60°C; In S3, the molar ratio of Li element in the lithium iron phosphate matrix to fructose and polyethylene glycol is 1:0.05:0.035; the temperature of the first stage of sintering is 500°C and the time is 5h; the temperature of the second stage of sintering is 750°C and the time is 8h.
[0105] Example 10 The difference between this embodiment and embodiment 3 is that the nozzle diameter in the high-pressure atomization mixing step is 0.4 mm, the operating pressure is 0.4 MPa; the high-speed stirring rate is 650 r / min; and the other steps and conditions remain unchanged.
[0106] Embodiment 11 The difference between this embodiment and embodiment 3 is that the insulation temperature in the electric blast oven is 170° C. and the insulation time is 9 hours; the other steps and conditions remain unchanged.
[0107] Example 12 The difference between this embodiment and embodiment 3 is that the temperature of the carbon source melting is 150° C., and the temperature of the gel water bath is 60° C.; the other steps and conditions remain unchanged.
[0108] Embodiment 13 The difference between this embodiment and embodiment 3 is that the temperature and time of the first stage of sintering are 450° C. and 3 h respectively, and the temperature and time of the second stage are 700° C. and 7 h respectively; the other steps and conditions remain unchanged.
[0109] Embodiment 14 The difference between this embodiment and embodiment 3 is that manganese chloride and ferric chloride are dispersed together in deionized water at a molar ratio of Fe to Mn of 0.985:0.015 to obtain a first solution; and the other steps and conditions remain unchanged.
[0110] Comparative Example 1 The difference between this comparative example and Example 3 is that: In S1, the molar ratio of Li element in lithium oxalate, Fe element in ferrous acetate and P element in ammonium hydrogen phosphate is 1:1:1.1; the nozzle diameter of the high-pressure atomizing spray gun is 0.6 mm, and the operating pressure is 0.2 MPa; the pH value is adjusted to 6; the insulation time in the electric blast oven is 9 hours; In S2, the melting temperature of rhamnose is 100°C; In S3, the molar ratio of Li element in the lithium iron phosphate matrix to rhamnose and polyethylene glycol is 1:0.03:0.02; the temperature of the first stage of sintering is 350°C; and the temperature of the second stage is 650°C.
[0111] Comparative Example 2 The difference between this comparative example and Example 3 is that the lithium iron phosphate matrix is prepared without using a high-pressure atomization mixing method, but directly mixing the materials and then reacting them.
[0112] Specific: S1: Directly disperse ferrous acetate, lithium oxalate and ammonium hydrogen phosphate in deionized water at a molar ratio of Li:Fe:P=1:1:0.95. After removing dissolved oxygen in the solution by blowing nitrogen for 30 minutes under stirring conditions, transfer the mixture to a stainless steel high-pressure reactor lined with polytetrafluoroethylene and place it in an electric blast oven at 150°C for 8 hours. After the reaction is completed, cool the product to room temperature and filter it. Wash the filtered solid phase by centrifugation with deionized water and anhydrous ethanol in turn, and finally dry it in a vacuum oven at 70°C for 12 hours to obtain a lithium iron phosphate precursor.
[0113] The steps and conditions of S2 and S3 are consistent with those of Example 3.
[0114] Comparative Example 3 The difference between this comparative example and Example 3 is that the carbon source is not melt-treated and is not compounded with polyethylene glycol gel.
[0115] Specific: The steps and conditions of S1 are consistent with those of Example 3.
[0116] S2: The lithium iron phosphate matrix and rhamnose in S1 (the molar ratio of lithium element to rhamnose in the lithium iron phosphate matrix particles is 1:0.035) are dispersed in anhydrous ethanol, and ball milled for 1.5 hours to mix evenly to obtain a mixed precursor; the mixed precursor is placed in a vacuum oven at 100°C and dried for 12 hours, and ground and crushed; then, the fully ground precursor is placed in a muffle furnace with high-purity argon gas for sintering, and the temperature is raised to 400°C at a rate of 5°C / min, and the insulation time is 2 hours; then the temperature is continued to be raised to 650°C, and the roasting time is 6 hours to obtain a lithium iron phosphate positive electrode material.
[0117] Comparative Example 4 The difference between this comparative example and Example 3 is that lithium iron phosphate is prepared directly by using a hydrothermal-high temperature calcination method.
[0118] Specifically, S1 of this comparative example is consistent with comparative example 2; S2 of this comparative example is basically consistent with comparative example 3, and the only difference is that the molar ratio of lithium element to rhamnose in the lithium iron phosphate matrix is 1:0.05.
[0119] Test example (1) The performance of the lithium iron phosphate positive electrode materials prepared in the above Examples 1 to 14 and Comparative Examples 1 to 4 was tested.
[0120] The performance test method is as follows: ①. Use FEI Tecnai F20 transmission electron microscope (TEM)-energy dispersive spectrometer (EDX) to test the thickness of the carbon coating layer of lithium iron phosphate cathode material and the content and distribution of carbon elements on the surface. Use the TEM imaging system to select the micro-region (local position) of a single lithium iron phosphate cathode material particle, and operate the electron microscope at high magnification to obtain a high-resolution image of the particle micro-region using the objective aperture. Then use the image acquisition system to measure and analyze the morphological image data of the particle to measure the coating thickness of the selected micro-region of the particle; at the same time, combine the EDX detector to qualitatively and quantitatively analyze the distribution of carbon elements on the surface of the selected micro-region of the particle. The sample collection quantity of the cathode material particles in the lithium iron phosphate cathode material sample is 10, which are randomly selected.
[0121] in, and s ( C wt% ) is calculated as follows: , , N 1 is the sample size of lithium iron phosphate cathode material particles taken for the test, which is 10; , , n For the i The sample size of the local position taken when testing the lithium iron phosphate positive electrode material particles is 5; d m The lithium iron phosphate positive electrode material particles are taken in the m The thickness of the carbon coating layer corresponding to a local position, Five local samples of lithium iron phosphate cathode material particles d m The average value of , in nm; C m The lithium iron phosphate positive electrode material particles are taken in the m The carbon content corresponding to each local position is The lithium iron phosphate positive electrode material particles 5 Local location samples C m The average value, in wt%.
[0122] The thickness of the carbon coating layer of the lithium iron phosphate cathode material is , the carbon content is .
[0123] ②. A FEI Tecnai F20 transmission electron microscope was used to observe the microstructure of the lithium iron phosphate positive electrode material particles and obtain their transmission electron microscope images (TEM two-dimensional projection images). ImageJ was used to perform shape analysis on the TEM two-dimensional projection images corresponding to the lithium iron phosphate positive electrode material particles, and parameters such as the two-dimensional projection area and the minimum circumscribed circle area of the projection were collected. The sample collection quantity of the positive electrode material particles in the lithium iron phosphate positive electrode material sample was 10, which were randomly selected.
[0124] in, The calculation method is as follows: , Defined as the first j The shape factor corresponding to each lithium iron phosphate positive electrode material particle is, is the diameter of a standard circle in the TEM two-dimensional projection image corresponding to the lithium iron phosphate positive electrode material particle, which is equal to the two-dimensional projection area of the lithium iron phosphate positive electrode material particle ( D s , μm) and the diameter of the minimum circumscribed circle of the two-dimensional projection of the lithium iron phosphate cathode material particle ( D , μm) ratio; N 2 is the sample size of the tested lithium iron phosphate positive electrode material particles, which is taken as 10.
[0125] ③. Specific surface area (BET) test: Use the Micromeritics ASAP2460 fully automatic specific surface analyzer to perform isothermal adsorption and desorption analysis using the static capacity method. The specific surface area of the lithium iron phosphate cathode material is determined by measuring the adsorption and desorption behavior of nitrogen. The unit is m 2 / g.
[0126] ④. Particle size: Use GSL-101BI laser particle size analyzer to test the particle size of lithium iron phosphate positive electrode material.
[0127] ⑤. Carrier mobility test: The carrier mobility of lithium iron phosphate positive electrode material is tested using HMS-7000 Hall effect tester. Carrier mobility is an important parameter to measure the conductivity of materials. It is used to characterize the speed of the movement of carriers (electrons and holes) inside and on the surface of lithium iron phosphate positive electrode materials under the action of unit electric field. The unit is cm 2 / V·s.
[0128] ⑥Electrochemical performance test A. Electrode preparation and button cell assembly: The lithium iron phosphate positive electrode material, the conductive agent acetylene black and the adhesive polyvinylidene fluoride were uniformly mixed in N-methylpyrrolidone at a mass ratio of 92:4:4 to form a slurry, which was then coated on an aluminum foil and dried in a vacuum drying oven. The slurry was then pressed into a positive electrode sheet using a tablet press. The negative electrode sheet was a metal lithium sheet. The electrolyte was 1 mol / L lithium hexafluorophosphate-ethylene carbonate: dimethyl carbonate (by volume, V (EC): V (DMC) = 1:1). A polypropylene porous membrane was used as a separator. The button cell was assembled in an argon glove box.
[0129] B. Electrochemical performance test: The assembled button cell is tested for electrochemical performance in the charge and discharge voltage range of 2.5V~4.5V. First, it is charged to 4.5V with constant current, and then discharged to 2.5V with rate current. The released capacity is the discharge capacity at the rate. After the discharge is completed, it is discharged to 2.5V with constant current again; then the next rate test is carried out.
[0130] ⑦. Electrode yield strength test: Use a universal testing machine with a video extensometer and a pneumatic foil fixture to test the yield strength (unit: MPa, i.e., the stress value that produces 0.2% residual deformation) of the lithium iron phosphate electrode sheet to evaluate the influence of the microscopic morphology of lithium iron phosphate particles and the surface carbon coating on the mechanical strength of the electrode. Use a pneumatic foil fixture to clamp the sample electrode, set the fixture air pressure between 0.4MPa and 0.6MPa, and perform a tensile test. Use a video extensometer to measure the deformation of the electrode sheet during the stretching process.
[0131] The above performance test results are shown in Table 1, Table 2, Figure 1 and Figure 2 shown.
[0132] Table 1 Test results
[0133] Table 2 Test results
[0134] from Figure 1 It can be seen that the lithium iron phosphate positive electrode material of Example 6 of the present invention has a regular morphology and a uniform thin carbon coating layer; Figure 2 It shows that the morphology of the lithium iron phosphate material of Comparative Example 4 is irregular and the surface carbon coating layer is also uneven, which is not conducive to improving the electrochemical performance of the positive electrode material.
[0135] From the data in Table 1, we can see that , as well as The size of the parameter factor of lithium iron phosphate material will Q Value affects.
[0136] It can be seen from Examples 1 to 9 that when the lithium iron phosphate positive electrode material particles The larger it is, that is, the closer it is to 1, the better the regularity of the particle morphology of the lithium iron phosphate cathode material; and The smaller the size, the more uniform the carbon coating layer in the lithium iron phosphate cathode material particles. The parameter factor obtained at this time Q The value is large, the parameter factor Q The size of will have a certain impact on the comprehensive electrochemical performance of lithium batteries prepared with lithium iron phosphate cathode materials. Generally, lithium iron phosphate cathode materials with regular morphology have good dispersibility, and can increase the compaction density of lithium iron phosphate cathode materials and reduce the internal resistance of the battery; uniform conductive carbon coating layers can effectively reduce the occurrence of side reactions between lithium iron phosphate cathode materials and electrolytes, and improve the diffusion and conduction of electrons and lithium ions, which will improve the electrical performance of batteries corresponding to lithium iron phosphate cathode materials.
[0137] From the data in Table 1 and Table 2, it can be seen that even if the lithium iron phosphate positive electrode materials have the same chemical composition, they will have different , as well as , which will correspond to parameter factors of different sizes Q When the parameter factor Q When the value is in the range of 0.07~7, and , as well as When both are within the preferred range ( 0.5~1, 0.05nm~0.35nm, is 0.02wt%~0.35wt%), at this time the battery corresponding to the lithium iron phosphate positive electrode material has good electrode yield strength, high specific capacity, and excellent rate performance and cycle performance.
[0138] Among them, Example 1 only as well as In the preferred range, the electrochemical performance and electrode yield strength of the battery made of the corresponding lithium iron phosphate positive electrode material are not as good as those of other embodiments; , as well as are all within the preferred range, but the parameter factor Q The electrochemical performance and electrode yield strength of the battery made of the corresponding lithium iron phosphate positive electrode material are improved compared with those of Example 1, but not as good as those of Examples 3 to 14; , , as well as Q All are within the preferred range. Compared with Examples 1-2, the electrochemical performance and electrode yield strength performance of the battery made of the corresponding lithium iron phosphate positive electrode material are significantly improved.
[0139] Furthermore, when the parameter factor of the lithium iron phosphate positive electrode material of Examples 3 to 9 is Q When the value is higher, the corresponding battery has better electrical performance. At this time, the lithium iron phosphate positive electrode material particles have a more regular morphology and a more uniform carbon coating layer, which is conducive to accelerating the lithium ion extraction / insertion rate, shortening the lithium ion transmission and diffusion path, increasing the conductivity of the lithium iron phosphate positive electrode material, and avoiding the occurrence of side reactions between the lithium iron phosphate positive electrode material and the electrolyte, thereby improving the charge and discharge performance of the lithium-ion battery.
[0140] In addition, the electrode yield strength corresponding to the lithium iron phosphate positive electrode material is determined by the microscopic morphology of the material particles and the carbon coating. The appropriate carbon content, regular particle morphology and uniform carbon coating are conducive to increasing the compaction density of the lithium iron phosphate positive electrode material particles, thereby improving the yield strength of the electrode prepared therefrom and enhancing the mechanical properties of the electrode. It can be seen from the data that, except for Example 4 and Example 9, the electrode yield strength values corresponding to the lithium iron phosphate positive electrode materials of the remaining examples increase with the parameter factor Q value increases; relatively speaking, although the parameter factors of Example 4 and Example 9 Q The value is within the preferred range, but its surface carbon content is slightly high, and more amorphous carbon is produced after high-temperature carbonization, which will reduce the compaction density of the lithium iron phosphate positive electrode material to a certain extent, and thus affect its electrode yield strength.
[0141] In addition, the lithium iron phosphate cathode material prepared in the example has a relatively good carrier mobility, indicating that the electrons inside and on the surface of the lithium iron phosphate cathode material have a relatively fast movement speed in the electric field per unit area, and further reflects that the carbon coating layer has a relatively good uniformity on the substrate surface. It can be seen from Examples 3-4, 8-9 and 6-7 that when the lithium iron phosphate cathode material as well as The smaller the value and the carbon content ( , wt%), the higher the carrier mobility of the lithium iron phosphate cathode material, which means that its conductivity is also better, which is beneficial to improving the charge and discharge performance of lithium batteries. as well as When the values are not much different, the apparent carrier mobility of Example 9 is slightly higher than that of Example 4, which is related to the lattice defects of lithium iron phosphate caused by element doping.
[0142] In addition, by comparing Examples 1 to 9 with Comparative Example 1, it can be seen that as well as The value is not within the scope provided by the present invention, although its The value is within the range provided by the present invention, and the corresponding apparent carrier mobility, electrochemical performance and electrode yield strength of the lithium iron phosphate positive electrode material are all poor. , , as well as Q When all are within the range provided by the present invention, the performance indicators of the obtained lithium iron phosphate positive electrode material will be more excellent.
[0143] It can be seen from Example 3 and Comparative Examples 2 and 4 that if the high-pressure atomization mixing method is not used in the preparation process, the The value is small and is quite different from that of Example 3, indicating that the shape regularity of the lithium iron phosphate positive electrode materials obtained in Comparative Examples 2 and 4 is poor, and the parameter factors in Comparative Examples 2 and 4 are Q The value is small, and the comprehensive electrochemical performance of the lithium iron phosphate positive electrode material is also low; the shape coefficient of the lithium iron phosphate positive electrode material prepared in Example 3 The value is large (less than 1), indicating that the particle morphology is relatively regular. This is due to the high-pressure atomization-high-speed stirring mixing operation mode, which provides crystal seeds with uniform particle size and morphology for the generation of lithium iron phosphate positive electrode materials. After the hydrothermal reaction process at an appropriate temperature, lithium iron phosphate precursor particles with good crystallinity and regular and uniform morphology are obtained. The corresponding electrochemical performance of the battery made of lithium iron phosphate positive electrode materials is also better.
[0144] Compared with Example 3, the nozzle diameter in the high-pressure atomization mixing step of Example 10 is smaller, the operating pressure is higher, and the stirring rate of the mixed liquid is faster, which is conducive to obtaining a seed precursor with a smaller particle size. The lithium iron phosphate precursor particles subsequently prepared by hydrothermal reaction have a larger specific surface area and better morphological regularity, which is conducive to shortening the diffusion path of lithium ions and increasing the lithium ion extraction / insertion rate, thereby enhancing the charge and discharge performance of the battery prepared corresponding to the lithium iron phosphate positive electrode material.
[0145] Compared with Example 3, the particle morphology regularity of the lithium iron phosphate positive electrode material of Example 11 is improved and the particle size is slightly reduced. This is because within the appropriate reaction temperature range, the increase in synthesis temperature makes the interaction between the reactants stronger, which accelerates the crystal growth process. At the same time, the higher temperature can provide sufficient energy to overcome the energy barrier required to form smaller particles, so that the formed crystal particles are smaller in size and more regular in morphology, which is beneficial to improve the electrochemical performance of the battery corresponding to the lithium iron phosphate positive electrode material.
[0146] Compared with Example 3, the shape coefficient of the lithium iron phosphate positive electrode material prepared in Example 14 is The value increases, because the appropriate amount of element doping can not only form crystal defects such as holes in the lithium iron phosphate lattice to reduce the resistance of lithium ion insertion / deinsertion, but also inhibit the growth of crystals in certain crystal directions or crystal planes, and further play a role in regulating the particle size and morphology of lithium iron phosphate particles. Therefore, lithium iron phosphate with better morphological regularity and larger specific surface area is obtained, which is beneficial to improving the electrochemical performance of the battery made corresponding to the lithium iron phosphate positive electrode material.
[0147] It can be seen from Example 3 and Comparative Examples 3 and 4 that if the carbon source is not melted or compounded with polyethylene glycol gel during the high-temperature calcination of lithium iron phosphate in the preparation process, the lithium iron phosphate positive electrode material prepared in Comparative Examples 3 and 4 and The value is large (greater than 0.9), indicating that the coating uniformity of the carbon coating layer in the positive electrode material is poor, so the apparent carrier mobility value of the material is low, and the obtained parameter factor Q The value is also small, and the overall performance of the positive electrode material is also low; the lithium iron phosphate positive electrode material prepared in Example 3 and The value is smaller (less than 0.5), indicating that the coating uniformity of the carbon coating layer in the positive electrode material is better. This is due to the co-infiltration and coating of the composite carbon source composed of the molten carbon source and the polyethylene glycol gel during the high-temperature calcination process, which is beneficial to further improve the electrochemical performance of the lithium iron phosphate positive electrode material.
[0148] Compared with Example 3, the lithium iron phosphate positive electrode material of Example 12 as well as The value is significantly reduced, indicating that the uniformity of the carbon coating on the surface of the lithium iron phosphate matrix is improved. This is because within the appropriate temperature range, a higher water bath temperature is conducive to increasing the strength and swelling properties of the polyethylene glycol gel, while a higher melting temperature is conducive to increasing the fluidity of the liquid carbon source. After the lithium iron phosphate matrix is mixed with the composite carbon source, the molten carbon source with high fluidity is conducive to being evenly and firmly coated on the surface of the lithium iron phosphate matrix by the high-strength polyethylene glycol, thereby increasing the uniformity of the carbon coating.
[0149] Compared with Example 3, the lithium iron phosphate positive electrode material of Example 13 as well as The value decreases and the thickness of the carbon coating increases slightly. This is because within a certain temperature range, a higher calcination temperature helps to form a more stable, continuous and compact carbon coating structure, thereby improving its coating uniformity and promoting the diffusion of lithium ions and the conduction of electrons; moreover, a higher sintering temperature will promote the rapid sintering of the carbon coating to a certain extent, thereby forming a thicker carbon layer. as well as The value shows that the carbon coating layer is more uniformly coated on the surface of the lithium iron phosphate matrix, which is beneficial to improving the electrochemical performance of the corresponding battery.
[0150] In summary, the lithium iron phosphate positive electrode material provided by the present invention has a regular particle morphology and a uniform carbon coating layer, which is beneficial to improving the carrier mobility and conductivity of the lithium iron phosphate positive electrode material, and is beneficial to further improving the electrochemical properties (such as specific capacity, rate and cycle performance, etc.) of the battery prepared from the lithium iron phosphate positive electrode material.
[0151] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A lithium iron phosphate positive electrode material, characterized in that: The lithium iron phosphate positive electrode material comprises a lithium iron phosphate matrix and a carbon coating layer coated on the surface of the lithium iron phosphate matrix; The average standard deviation of the thickness of the carbon coating layer in the lithium iron phosphate positive electrode material is , , 0.05nm≤ σ(d) ≤0.35nm; The average standard deviation of the carbon content in the lithium iron phosphate positive electrode material is σ ( C wt% ), , 0.02wt%≤ σ(C wt% ) ≤0.35wt%; in, N 1 is the sample amount of lithium iron phosphate positive electrode material particles taken during the test of the lithium iron phosphate positive electrode material, N 1 ≥ 10; , The first value taken when testing the lithium iron phosphate positive electrode material i The standard deviation of carbon coating thickness and carbon content corresponding to each lithium iron phosphate cathode material particle; , , n For the i The sample size of a local location taken when testing a lithium iron phosphate positive electrode material particle, n ≥5; d m For the m The thickness of the carbon coating layer corresponding to a local position, For what is taken n Local location samples d m The average value of , in nm; C m For the m The carbon content corresponding to each local position is For what is taken n Local location samples C m The average value, in wt%; The thickness of the carbon coating layer of the lithium iron phosphate positive electrode material is d , , 1nm≤ d ≤10nm; For the i The lithium iron phosphate positive electrode material particles are taken n Local location samples d m The average value of The carbon content of the lithium iron phosphate positive electrode material is , , 1wt%≤ C ≤10wt%; For the i The lithium iron phosphate positive electrode material particles are taken n Local location samples C m The average value of .
2. The lithium iron phosphate positive electrode material according to claim 1, characterized in that: The shape factor of the lithium iron phosphate positive electrode material is , , 0.5≤ ≤1; in, N 2 is the sample amount of lithium iron phosphate positive electrode material particles taken during the test of the lithium iron phosphate positive electrode material, N 2 ≥ 10; The first value taken when testing the lithium iron phosphate positive electrode material j The shape factor corresponding to each lithium iron phosphate cathode material particle; , D s For the j The diameter of the standard circle with the same projection area in the TEM two-dimensional projection image of each lithium iron phosphate positive electrode material particle, D For the said j The diameter of the minimum circumscribed circle of the particle projection in the TEM two-dimensional projection image of a lithium iron phosphate positive electrode material particle.
3. The lithium iron phosphate positive electrode material according to claim 2, characterized in that: The parameter factors of the lithium iron phosphate positive electrode material Q = , 0.07nm -1 ≤ Q ≤7nm -1 .
4. The lithium iron phosphate positive electrode material according to any one of claims 1 to 3, characterized in that The lithium iron phosphate positive electrode material also includes at least one of the following features: Feature 1: The lithium iron phosphate positive electrode material 0.550~0.910; Feature 2: The lithium iron phosphate positive electrode material 1.5nm~9.1nm; Feature 3: The lithium iron phosphate positive electrode material 0.055nm~0.343nm; Feature 4: The lithium iron phosphate positive electrode material 1.94wt%~9.68wt%; Feature 5: The lithium iron phosphate positive electrode material σ ( C wt% ) is 0.024wt%~0.336wt%; Feature 6: The lithium iron phosphate positive electrode material Q 0.072nm -1 ~6.596nm -1 ; Feature 7: The specific surface area of the lithium iron phosphate positive electrode material is 9.3m 2 / g~15.1m 2 / g; feature 8: The lithium iron phosphate positive electrode material D 50 0.85μm~1.50μm; Feature 9: The carrier mobility of the lithium iron phosphate positive electrode material is 20.03×10 -6 cm 2 / V·s~21.71×10 - 6 cm 2 / V·s; feature 10: The general formula of the lithium iron phosphate matrix is Li 1-x A x Fe 1-y M y (PO 4-a )D a ; wherein A includes at least one of Na and Mg; M includes at least one of Al, Ni, Co, Mn, Ti, La, Ce, Cr, Mo, Ca, Ga, V, Nb, Zr, In, Zn and Y; D includes at least one of F and S; 0≤x≤0.1, 0≤y≤0.1 and 0≤a≤0.
1.
5. A method for preparing the lithium iron phosphate positive electrode material according to any one of claims 1 to 4, characterized in that: The method comprises the following steps: ball-milling a lithium iron phosphate matrix and a composite carbon source to obtain a mixed precursor; and drying and sintering the mixed precursor to obtain a lithium iron phosphate positive electrode material.
6. The preparation method according to claim 5, characterized in that: The preparation of the lithium iron phosphate positive electrode material includes at least one of the following features: Feature 11: The preparation of the lithium iron phosphate matrix comprises: mixing a first solution containing a ferrous salt with a second solution containing a lithium source and a phosphate to obtain a mixed solution; adjusting the pH value of the mixed solution to 6-8 and then performing a hydrothermal reaction, and collecting a solid after the reaction is completed; Feature 12: The preparation of the composite carbon source comprises: mixing polyethylene glycol gel with a melted carbon source; wherein the carbon source comprises at least one of sorbitol, erythritol, fructose, rhamnose and malic acid; and the molar ratio of the lithium element in the lithium iron phosphate matrix to the carbon source and the polyethylene glycol is 1:(0.03-0.05):(0.02-0.04); Feature 13: The ball milling time is 1h~2h; Feature 14: The drying temperature of the mixed precursor is 90°C to 110°C; Feature 15: The drying time of the mixed precursor is 10h~14h; Feature 16: The sintering includes: first keeping warm at 400°C to 550°C for 2h to 5h, and then keeping warm at 650°C to 750°C for 6h to 8h.
7. The preparation method according to claim 6, characterized in that: The preparation of the lithium iron phosphate matrix includes at least one of the following conditions: Condition 1: The general formula of the lithium iron phosphate matrix is Li 1-x A x Fe 1-y M y (PO 4-a )D a , when the lithium iron phosphate matrix contains M, A and D elements, the first solution further contains an M source, and the second solution further contains an A source and a D source; Condition 2: spraying the first solution into the second solution under stirring by high-pressure atomization; or, spraying the second solution into the first solution under stirring by high-pressure atomization; Condition 3: The temperature of the hydrothermal reaction is 150°C to 180°C; Condition 4: The hydrothermal reaction time is 8h~10h.
8. The preparation method according to claim 7, characterized in that: The ferrous salt includes at least one of ferrous oxalate, ferrous chloride and ferrous acetate; Or, the lithium source includes at least one of lithium oxalate, lithium chloride and lithium acetate; Or, the phosphate includes at least one of diammonium phosphate and ammonium hydrogen phosphate; Or, the M source is a water-soluble salt of the M element; Or, the A source includes at least one of sodium fluoride, magnesium fluoride, sodium chloride, magnesium chloride and sodium sulfide; Or, the D source includes at least one of ammonium fluoride, lithium fluoride, ammonium sulfide, lithium sulfide, ammonium bisulfite and thiourea; Or, the ratio of the total molar number of the iron element in the ferrous salt to the M element in the M source, the total molar number of the lithium element in the lithium source to the A element in the A source, and the molar number of the P element in the phosphate is 1:1:(0.95-1.1); wherein the molar ratio of the lithium element to the A element is (0.9-1):(0-0.1); the molar ratio of the iron element to the M element is (0.9-1):(0-0.1); the molar ratio of the oxygen element in the phosphate to the D element in the D source is (3.9-4):(0-0.1); Or, the nozzle diameter of the high-pressure atomization spray gun used for the high-pressure atomization is 0.3mm~0.6mm, and the operating pressure is 0.2MPa~0.4MPa; Alternatively, the stirring condition corresponds to a stirring rate of 600 r / min to 1000 r / min.
9. A positive electrode sheet, characterized in that: The active material in the positive electrode sheet includes the lithium iron phosphate positive electrode material according to any one of claims 1 to 4.
10. A battery, characterized in that: The battery comprises the positive electrode sheet according to claim 9.
Citation Information
Patent Citations
Lithium ion phosphate positive electrode material of nanometer core shell structure and preparation method thereof
CN102420324A
Self-repairing type high-nickel ternary lithium-battery electrode material with long service life and preparation method
CN108376775A
Production method and continuous production device of nickel cobalt lithium manganate anode material
CN110282664A
Active material for secondary battery electrode and secondary battery using same
CN114930580A
Lithium manganese iron phosphate material, composite carbon source coating method and application
CN117913265A
Cited By
Homogeneous lithium iron phosphate material prepared by interface strengthening and application of homogeneous lithium iron phosphate material
CN120483091A
Interface reinforced preparation of homogeneous lithium iron phosphate material and application thereof
CN120483091B
Lithium iron phosphate positive electrode material, preparation method and pole piece
CN121076125A
Phosphate positive electrode material, preparation method thereof and battery
CN121292393A
Lithium iron phosphate positive electrode material, and preparation method therefor and use thereof
EP4779713A1
